COVALENT IMMOBILIZATION OF LIPASES ON ACTIVATED HOLLOW SILICA MICROSPHERES - SZOKOL, Bianka; HORNYÁNSZKY, Gábor; NAGY, József (Studia Universitatis Babeș-Bolyai Chemia, 2019)
This study explores the covalent immobilization of three lipases (Lipase AK, from Pseudomonas fluorescens; Lipase PS, from Burkholderia cepacia; and CrL, from Candida rugosa) on four supports prepared by functionalization of mesoporous hollow silica microspheres (M540) with various bisepoxides as activating agents for production of novel lipase biocatalysts for enantiomer selective biotransformations of secondary alcohols. The influence of length, rigidity and hydrophobicity of the bisepoxide activating agents was investigated on the efficiency of immobilization and catalytic properties of the resulted twelve lipase biocatalysts. The hollow silica particles modified with the most beneficial bisepoxide activating agents resulted in novel biocatalysts capable for kinetic resolution of racemic 1-phenylethanol rac-1a and racemic octan-2-ol rac-1b with high activity and enantioselectivity.